First nationwide antimicrobial susceptibility surveillance for Neisseria gonorrhoeae in Brazil, 2015–16. (4th April 2018) - Bazzo, M L; Golfetto, L; Gaspar, P C; Pires, A F; Ramos, M C; Franchini, M; Ferreira, W A; Unemo, M; Benzaken, A S; ,
Abstract: Objectives: Gonorrhoea and antimicrobial resistance (AMR) in Neisseria gonorrhoeae are major public health concerns globally. Enhanced AMR surveillance for gonococci is essential worldwide; however, recent quality-assured gonococcal AMR surveillance in Latin America, including Brazil, has been limited. Our aims were to (i) establish the first nationwide gonococcal AMR surveillance, quality assured according to WHO standards, in Brazil, and (ii) describe the antimicrobial susceptibility of clinical gonococcal isolates collected from 2015 to 2016 in all five main regions (seven sentinel sites) of Brazil. Methods: Gonococcal isolates from 550 men with urethral discharge were examined for susceptibility to ceftriaxone, cefixime, azithromycin, ciprofloxacin, benzylpenicillin and tetracycline using the agar dilution method, according to CLSI recommendations and quality assured according to WHO standards. Results: The levels of resistance (intermediate susceptibility) to tetracycline, ciprofloxacin, benzylpenicillin and azithromycin were 61.6% (34.2%), 55.6% (0.5%), 37.1% (60.4%) and 6.9% (8.9%), respectively. All isolates were susceptible to ceftriaxone and cefixime using the US CLSI breakpoints. However, according to the European EUCAST cefixime breakpoints, 0.2% ( n = 1) of isolates were cefixime resistant and 6.9% ( n = 38) of isolates had a cefixime MIC bordering on resistance. Conclusions: This study describes the first national surveillance of gonococcal AMR in Brazil, which was quality assured according to WHO standards. The high resistance to ciprofloxacin (which promptly informed a revision of the Brazilian sexually transmitted infection treatment guideline), emerging resistance to azithromycin and decreasing susceptibility to extended-spectrum cephalosporins necessitate continuous surveillance of gonococcal AMR and ideally treatment failures, and increased awareness when prescribing treatment in Brazil.